Desmoplastic reaction in the microenvironment of head and neck and other solid tumors: the therapeutic barrier - Kohei Okuyama; Maiko Tsuchiya; Kala Chand Debnath; Shajedul Islam; Souichi Yanamoto (Therapeutic Advances in Medical Oncology)
Head and neck squamous cell carcinoma (HNSCC) remains a challenge due to limited prognostic biomarkers and therapeutic options. The tumor microenvironment (TME), particularly the desmoplastic reaction (DR) characterized by stromal fibrosis, plays a crucial role in cancer progression and resistance to therapy. This review aims to summarize the biological significance of DR in HNSCC initiation, progression, and treatment resistance. Histologically, DR in HNSCC correlates with invasion patterns and clinical outcomes, affecting disease-free and overall survival. The interaction between cancer-associated fibroblasts (CAFs) and TME influences immune responses, including resistance to immunotherapy. Notably, human papillomavirus-driven HNSCC exhibits distinct DR characteristics that further influence the prognosis. DR promotes epithelial-mesenchymal transition and cancer cell invasion through CAF-mediated extracellular matrix remodeling and signaling pathways such as transforming growth factor-beta. DR also affects bone invasion and chemotherapy resistance by modulating stromal responses. Therapeutic strategies targeting DR and stromal components show promise in overcoming therapeutic resistance including resistance to immune checkpoint inhibitors. Understanding the role of DR in HNSCC biology and its impact on treatment response is critical to developing effective therapeutic interventions.